Negotiating Ethnic Segregation through Political and Cultural Boundaries: A Case Study of the Mawanella Divisional Secretariat Division - Kithsiri, T.; Senevirathne, W. (Faculty of arts university of jaffna, 2025)
Massey and Denton (1993) describe ethnic segregation as physical separation. But, it takes various form like social, residential and even psychological also. Hence it creates boundaries in the area. Here, this study focused on political and cultural boundaries. Bashkow (2004) explains that cultural boundaries are invisible lines that divide different cultural groups. While Drew (2004) said that political boundaries are formal legally recognized divisions of space. Cultural boundaries do not always follow political boundaries but political boundaries are influenced by cultural boundaries. Studies on ethnic segregation in Sri Lanka so far have mainly focused on segregation across the country and in urban centres. However, there is a gap in the amount of research that has been conducted on how this ethnic segregation affects suburban and rural areas. Furthermore, most of these studies focused on the historical roots of these ethnic tensions (Tambiah, 1996), the impact of language policies (De Silva, 1986), and the consequences of long-term conflict on intercommunal relations (Höglund and Orjuela, 2011) related to this topic but, there has been less comprehensive study of the contribution of ethnic segregation to shaping the political and cultural boundaries of everyday life. This research aims to investigate ethnic segregation at the micro level, examining how ethnic segregation actively shapes and how people experience these political and cultural boundaries in Mawanella.